Swasembada Pangan sebagai Pilar Strategis Ketahanan Nasional di Indonesia dalam Perspektif Manajemen Pertahanan - Dwi Agustini Herawati; Agung Risdhianto; Edy Saptono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Food security is a strategic component in strengthening national resilience, particularly in addressing complex and multidimensional non-military threats. In the Indonesian context, food security is closely linked to social stability, national security, and sustainable development. This study aims to analyze the concept of food self-sufficiency as a pillar of Indonesian national resilience from a defense management perspective. The method used is a qualitative descriptive approach with a literature review approach, utilizing various sources such as academic journals, government policy documents, and reports from related institutions. The results of the study indicate that Indonesia has not yet fully achieved food self-sufficiency, marked by the continued high dependence on imports of strategic food commodities such as wheat, soybeans, and beef. Furthermore, national programs such as the food estate program have not been running optimally due to technical issues, governance, and weak cross-sectoral coordination. The analysis also reveals that the six pillars of food security developed by the FAO—availability, access, utilization, stability, sustainability, and governance—have not been fully integrated effectively into national policies. From a defense management perspective, achieving food self-sufficiency requires a systematic strategy, encompassing long-term planning based on risk analysis, cross-ministerial and private sector organization, integrated implementation supported by modern agricultural technology, and adaptive oversight capable of responding to the dynamics of climate change and global markets. This approach not only strengthens the agricultural sector but also strengthens the nation's defense capacity against non-military threats such as food crises, natural disasters, and economic instability. Therefore, food self-sufficiency must be positioned as an integral part of a sustainable and resilient national defense system, capable of supporting national independence while safeguarding national sovereignty amid increasingly complex global challenges.